Disinformation in the new media system - characteristics, forms, reasons for its dissemination and potential means of tackling the issue - Levak, Tomislav (Array, 2021)
This paper aims to explain the phenomenon of disinformation and its impact. Furthermore, it aims to point out the magnitude and seriousness of the problem, as well as the importance of joint action of all social structures in solving it. The design, production, and dissemination (mainly orally) of untrue and inaccurate information and news for various purposes have been recorded since ancient times. After the invention of the printing machine, their continuous reproduction and distribution began in written form, which also enabled them to have a stronger impact, longer duration, and greater reach. Thanks to the development of the media, especially the mass media such as newspapers, radio, and television, information and news spread faster, more easily and farther, but at the same time, disinformation began to appear in the public sphere more often. Due to the strong development of technology and the emergence of new digital media, primarily the Internet, social networks, and communication platforms, as global communication phenomena, this problem has reached worrying, and often dangerous, levels in the current digital age and the new media system. According to recent indicators and research, the situation is deteriorating. Although the number of papers and the amount of research on this topic has significantly increased in Europe and the world in recent years, it is a complex issue which is still not sufficiently addressed in the scientific discourse. Therefore, this paper attempts to provide a clear insight into the definitions and characteristics of disinformation, as a concept that was officially adopted at the European Union level, for the purpose of denoting the phenomenon, along with related and similar terms such as fake news, misinformation, malinformation, information disorder, information pollution, alternative facts and others.